1982
DOI: 10.1056/nejm198204293061703
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Features of Chronic Atrial Fibrillation

Abstract: In the Framingham Study 2325 men and 2866 women 30 to 62 years old at entry were followed biennially over 22 years for the development of chronic atrial fibrillation in relation to antecedent cardiovascular disease and risk factors. During surveillance, atrial fibrillation developed in 49 men and 49 women. The incidence rose sharply with age but did not differ significantly between the sexes. Overall, there was a 2.0 per cent chance that the disorder would develop in two decades. Atrial fibrillation usually fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
870
8
88

Year Published

1989
1989
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,174 publications
(994 citation statements)
references
References 9 publications
28
870
8
88
Order By: Relevance
“…8,10,11 The ability to predict progression from paroxysmal to persistent AF is therefore also important clinically. Previous studies have identified disease duration, 4 left ventricular dysfunction, 12 enlarged left atrial dimension, 13 advanced age, 14 prolongation of FPD, 13 and a low root mean square voltage for the last 30 ms of the filtered P wave 13 as indicators of transition from paroxysmal to persistent AF. How-72 Abbreviations: ECG = electrocardiogram, P-SAECG = P-wavetriggered signal-averaged electrocardiogram, FPD = filtered P-wave duration, RMS30 = root mean square voltage for the last 30 ms of filtered P-wave, Echo = echocardiogram, LAD = left atrial dimension, LVDd = left ventricular end-diastolic dimension, LVEF = left ventricular ejection fraction.…”
Section: Discussion Prediction Of Transition To Persistent Atrial Fibmentioning
confidence: 99%
See 1 more Smart Citation
“…8,10,11 The ability to predict progression from paroxysmal to persistent AF is therefore also important clinically. Previous studies have identified disease duration, 4 left ventricular dysfunction, 12 enlarged left atrial dimension, 13 advanced age, 14 prolongation of FPD, 13 and a low root mean square voltage for the last 30 ms of the filtered P wave 13 as indicators of transition from paroxysmal to persistent AF. How-72 Abbreviations: ECG = electrocardiogram, P-SAECG = P-wavetriggered signal-averaged electrocardiogram, FPD = filtered P-wave duration, RMS30 = root mean square voltage for the last 30 ms of filtered P-wave, Echo = echocardiogram, LAD = left atrial dimension, LVDd = left ventricular end-diastolic dimension, LVEF = left ventricular ejection fraction.…”
Section: Discussion Prediction Of Transition To Persistent Atrial Fibmentioning
confidence: 99%
“…Studies have previously been conducted to identify factors predictive of progression from paroxysmal to persistent AF. 4,[12][13][14] However, further investigation is required, since most of these studies did not investigate predictive accuracy for transition to persistent AF and some used the results of only short-term follow-up. The present prospective study was conducted for identifying indicators capable of predicting progression from paroxysmal to persistent AF based on longterm follow-up, and to examine the predictive accuracy of those indicators.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension is a well-established, independent risk factor for AF, 9,279,321,322 and this risk increases in patients with uncontrolled systolic BP, 323 particularly in those with EF less than 40%. 324 Even BPs that are near the upper limit of normal (systolic 130–139 mm Hg, diastolic 85–89 mm Hg) predict risk for AF in healthy middle-aged men 325 and women.…”
Section: Section 3: Modifiable Risk Factors For Af and Impact On Ablamentioning
confidence: 99%
“…It affects more than 10% of people over age 80 and is often associated with cardiovascular disease. 2 Based on Framingham Heart Study data, a person’s lifetime risk of developing it is about 25%. 3 …”
Section: One In Four Peoplementioning
confidence: 99%